ANALISIS MOTIVASI GURU PADA PROSES PEMBELAJARAN SOSIOLOGI KELAS XI IIS SMA MUHAMMADIYAH 2 PONTIANAK - Ahmad, Ali; Salim, Izhar; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is entitled "Motivation Analysis of Teachers in the Learning Process of Sociology Class XI IIS 2 Muhammadiyah High School in Pontianak". A common problem in this research is how the motivation of teachers in the learning process of sociology in class XI IIS of Muhammadiyah 2 High School Pontianak ?. The purpose of this study was to find out how the teacher's motivation and the form of motivation that the teacher dominantly used in the Sociology learning process. This study uses a descriptive method with a qualitative approach. The data sources are sociology teachers and 4 students. Data collection techniques are observation, interview and documentation study. Data collection tool in the form of interview guides, observation and documentation guides. Data analysis techniques in this study included data reduction, data presentation and verification / conclusion. The results of the study showed the following findings: (1) The form of motivation that the teacher uses in the Sociology learning process that is giving hope, explaining learning goals, helping the difficulties that occur, and gifts and praise. (2) the dominant form of motivation the teacher does in the sociology learning process is helping the difficulties that occur, giving gifts and praise.Keywords: Learning proces, Teacher Motivation